Shengxian decoction alleviates cyclophosphamide-induced immunosuppression via improving B cell-mediated immune responses - Yang, Chengyu; Xu, Ya; Gong, Fenfang; Li, Silu; Zhan, Huang; Huang, Zhixuan; Wang, Maolin; Li, Hui; Huang, Hengjun (Frontiers in Pharmacology, 2025)
BackgroundChemotherapy is a prevalent and extensively utilized cancer treatment modality. However, it can result in immunosuppression. Shengxian Decoction (SXD) is a Traditional Chinese Medicine formula that has been demonstrated to improve immunosuppression caused by chemotherapy in clinical settings. Nevertheless, the therapeutic evaluation and mechanism of SXD in regulating immunosuppression remain unclear. The aim of this study was to ascertain the efficacy of SXD in immunocompromised mice and to elucidate the underlying immunological mechanisms.MethodsThe immunosuppression mouse model was generated through the administration of cyclophosphamide for 3 days. After that, the mice were treated by SXD extracts at doses of 0.47 and 0.94 g/kg/day, respectively. The spleen, thymus and blood of mice were collected for evaluation of drug efficacy. The population of B and T cells was detected by flow cytometry. The genes regulated by SXD in spleen were identified by utilizing RNA sequencing. The Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment were used to analyze the signaling pathway modulated by SXD. The protein expression of B cell transcription factors was detected by the immunoblotting. The signaling pathways modulated by SXD were elucidated using transcriptomics analysis complemented by network analysis.ResultsSXD treatment ameliorates decreased splenic and thymic organ indexes, as well as decreased lymphocyte number in the spleen in immunosuppressed mice. ELISA assay and flow cytometry shows that SXD promotes attenuate B-cell-mediated humoral immune responses. The RNA sequencing reveals that SXD primarily upregulates the B cell-mediated immune response and B cell receptor signaling pathway. SXD treatment upregulates the expression of B cell differentiation factors Pax5, Tcf3 and promotes splenic cell proliferation. Furthermore, SXD extract significantly inhibits hypoxia and senescence pathways in the spleen.ConclusionSXD exerts a protective effect against CTX-induced immunosuppression by upregulating B cell immunity and inhibiting hypoxia and senescence pathways.